Social Exclusion of Aged Transgender in Pakistan: A Case Study of District Rawalpindi - Nadir Shahzad, Muhammad; Hussain Bhutta, Mazhar; Khan, Sarfraz; Rafiq , Nazia; Ramzan, Samreena (International Journal of Psychosocial Rehabilitation, 2020)
Ageism is known as discrimination and stereotyping against older people. A transgender person is considered neither male nor female or a combination of both male and female. The transgender population, being a marginalized community in Pakistan, has to face multiple problems (i.e., economic, psychological, and health) with the increase in age. In this vein, the current study was conducted to explore the socio-economic and health conditions of aged transgender people in the Rawalpindi district of Punjab province. Specifically, this study aimed to assess the extent of this population's access to basic human rights such as health, food, shelter, clothing, and sanitation. Least research has been done in Pakistan in this regard. Therefore, the case studies method was used for data collection. A sample of nine transgender people with an age above 50 years was selected through the snowball sampling technique. The result indicates that usually aged transgender people were living in extreme alarming situations. Findings indicate that most of the older transgender profession was beggary, and 55.6% (n = 5) of the transgender fall into the category of low income. Most of the transgender health status was unpleasant due to lack of devotion. Likewise, 89.9% (n = 8) transgender people lived in rented houses and paid double the fair because people stigmatized them for questionable professions like dancing and sex work. The study has also shown that all aged transgender people have an imbalanced diet, poor condition of seasonal clothes, and a poor sanitation system because they live in the side areas of the city due to gender non-conforming. The study suggests further work on aged transgender people and mainstreaming them in the sociological, anthropological, and human rights context.